Analisis Pengendalian Produk Cacat pada Kain Spunbond dengan Pendekatan Six Sigma di PT. X - Renaldyani Iswanto; Yitno Utomo (CV. ALIM'SPUBLISHING, 2026)
Product quality is a key factor in improving the competitiveness of manufacturing companies. PT. X, a spunbond fabric manufacturer, continues to face product defects that affect production quality. This study aims to identify Critical to Quality (CTQ) characteristics, determine the dominant defect types, measure process capability using the Six Sigma method, and propose quality improvement recommendations. The study used all production and defect data as the population, with six months of production data (May–October 2025) selected through purposive sampling based on data availability and completeness. Data were analyzed using the Six Sigma approach, including CTQ analysis, Pareto diagrams, P-Charts, Defects Per Million Opportunities (DPMO), sigma level calculations, and fishbone diagrams. The results indicate that Black Cont (D1), Fil Drop (D7), and Cont Net (D3) are the dominant defects, contributing approximately 92% of total defects. The DPMO values ranged from 12,755,102 to 17,699,115, with sigma levels between 3.87 and 3.99, indicating that the production process performs reasonably well but still requires quality improvement. The novelty of this study lies in the integrated application of Six Sigma to prioritize quality improvement in spunbond fabric production. The findings provide practical recommendations, including improving operator competence, machine maintenance, SOP implementation, raw material quality control, inspection systems, and production environment management to reduce product defects.